Linking bioclimatic theory and environmental performance in its climatic and cultural context: an analysis into the tropical highrises of Ken Yeang - Jahn Kassim, Puteri Shireen; Ip, Kenneth (2006)
This paper presents the outcome of an environmental performance analysis and theoretical study into the bioclimatic highrises of Malaysian architect Ken Yeang – with a focus on the tropical climate. By focusing on case studies representing the three main phases of Yeang’s work, the impact of features such as core placement, sky courts, balconies, shading system and vegetation system are evaluated in terms of cooling and total energy use under the Malaysian climate. The climatic performances of the bioclimatic high-rise envelopes are then tested through comparisons with generic highrise forms. The study highlights the link between bioclimatic theories and climatic ‘performances’ and any conflicts between them. A paradox between theories based on critical regionalism and bioclimatic intentions are also described. Yeang’s designs are then evaluated in terms of overall forms rather than separate components. The study then focuses on the debate on critical regionalism and sustainable design, the balance of modernization and traditional values within the context of developing cities, and the significance of bioclimatic and critical regionalist th